Wind energy modeling and simulation. Volume 1, - Veers, Paul S. (Institution of Engineering and Technology, 2019)
The book consists of 9 chapters and covers the following topics: exascale computing; blade-resolved modeling; mesoscale atmosphere modeling; wind plant simulation; atmospheric turbulence modelling; wind-farm flows; wind-plant-controller design; wind power forecasting and wind energy modeling.
Keywords: Wind power -- Computer simulation.; Wind power plants -- Computer simulation.; elektronické knihy; electronic books